Kikuchi-Fujimoto Disease: An Atypical Presentation of a Rare Disease - Moyer, Amanda (Cureus, 2019)
Kikuchi-Fujimoto disease (KFD), or necrotizing histiocytic lymphadenitis, is a rare cause of lymphadenopathy and fever. Although the clinical course is usually benign, KFD is often mistaken for malignancy or infection. Recognition of typical and atypical cases of KFD is necessary to avoid unnecessary interventions. Here we report an atypical presentation of KFD with diffuse lymphadenopathy and leukocytosis associated with high levels of circulating Epstein-Barr viral DNA.